The Evolution of India’s Knowledge System: Implications for 21st-Century Education - Maiti, Jayati (Journal of Research in Innovative Teaching and Inclusive Learning, 2026)
India's knowledge system has evolved over millennia, rooted in ancient traditions and philosophies, such as Vedas, Upanishads, and diverse regional practices. Over time, this knowledge system integrated various influences, including Islamic, colonial, and modern Western educational frameworks. Today, the challenge lies in adapting this rich legacy to meet the demands of 21st-century education. With rapid technological advancements, shifting global dynamics, and a diverse societal fabric, India must innovate while preserving its cultural heritage. The evolution of the Indian knowledge system provides unique opportunities to integrate traditional wisdom with contemporary pedagogies, ensuring that education fosters creativity, critical thinking, and holistic development. The historical evolution of India's knowledge system and examines its implications for modern education, focusing on how to blend ancient wisdom with 21st-century needs for a more inclusive, sustainable, and forward-looking education system.